Effect of Diffusates of Parthenium hysterophorous on Seed Germination of Raphanus sativus L. - Paudel, VR; Gupta, VNP; Agarwal, VP (Scientific World, 2010)
The present investigation focused on the effects of plant and seed diffusates of Parthenium hysterophorus L. on seed germination of Raphanus sativus L. Level of glucose in germinating seeds as an indirect measure of amylase activity was estimated. About 91.66% viable seed of Raphanus sativus were treated in different concentrations of rhizospheric soil diffusates (PD) and germinating seed diffusates (SD) of Parthenium hysterophorus. Both diffusates were found effective to retard and minimize the germination of Raphanus seeds. The maximum inhibition for both cases was found at 100 % concentrations of the diffusates. The correlation analysis revealed the correlation factor - 0.784 between PD concentrations and Raphanus seed germination and that of - 0.889 between SD concentrations and Raphanus seed germination with 5% level of significance. This indicated that the increase in concentrations played negative role in germination process of Raphanus seeds. The results were interpreted in terms of the possible roles of "Parthenin", a sesquiterpene-lactone which is known to be present in Parthenium hysterophorus. Key words: Sesquiterpenes; Allelopathy; Parthenin. DOI: 10.3126/sw.v7i7.3820 Scientific World Vol.7(7) 2009 pp.29-32